Institutionalizing Gender and Social Inclusion in Climate Information Services: Lessons from AGRHYMET journey under AICCRA - Kaboré, Assétou; Obossou, Abrewa Remilokoun Esdras; Ali, Abdou; Alhassane, Agali; Segnon, Alcade Christel; Zougmore, Robert Bellarmin (2025)
Over the past five years, AGRHYMET, in partnership with AICCRA, has implemented a range of flagship activities in West Africa and the Sahel aimed at promoting and scaling climate information services. This InfoNote documents and shares practical lessons learned from the mainstreaming of gender considerations in these activities. Integrating gender and social inclusion across activities has led to greater participation, stronger leadership, and better learning outcomes among women and youth. Adopting gender-accommodative measures, such as supporting breastfeeding mothers and their caregivers, has improved equitable participation and helped remove long-standing barriers for women in technical training environments. Institutionalizing gender and social inclusion practices in technical capacity building can be achieved by moving beyond the collection of sex-disaggregated data to embrace an intersectional data approach, strengthening mentorship and visibility for women professionals, and embedding inclusive governance mechanisms.